Reformulation of State Defense Policy Management Based on AI Technology for Decision Making in State Defense - Widiyanto Saputro; Asep Adang Supriyadi; Guntur Eko (Universitas Pendidikan Indonesia, 2025)
The rapid advancement of Artificial Intelligence (AI) has significantly influenced global military strategies, leading to a paradigm shift in national defense policies. Countries such as the United States, China, and Russia have integrated AI into their defense frameworks, utilizing autonomous systems, cyber defense, and AI-driven decision-making processes. However, Indonesia’s current defense policy remains heavily reliant on conventional approaches, necessitating an adaptive reformulation to incorporate AI technologies. This study employs a qualitative analytical approach, utilizing a thematic content analysis of 41 peer-reviewed journals sourced from Scopus and Elsevier. The research focuses on AI integration in national defense, strategic decision-making frameworks, cybersecurity policies, and ethical considerations. By examining AI-driven military applications and governance structures, this study aims to present actionable insights for policy reform. AI enhances military efficiency by enabling rapid decision-making, real-time intelligence analysis, and predictive modeling for conflict scenarios. However, challenges such as ethical dilemmas, cybersecurity vulnerabilities, and adversarial learning risks remain pressing concerns. Indonesia faces constraints in infrastructure, regulatory frameworks, and technological expertise, requiring immediate policy intervention to align national defense strategies with AI advancements. Reformulating Indonesia’s defense policy to integrate AI is crucial for ensuring national security resilience in the digital era. The study recommends establishing a National AI Defense Agency, developing robust cybersecurity mechanisms, and enforcing ethical guidelines for autonomous military applications.